Rancangan Self Evaluation dengan Media E-Filling untuk Sertifikasi ISO 9001:2015 - Natanael Tedjakusuma; I Nyoman Sutapa; Indriati Njoto Bisono (Jurnal Titra, 2021)
This study discusses the design of a self-evaluation program with a media called e-filling for ISO 9001:2015. in this e-filling program, it is useful to help an organization create an internal management system faster, easier, and without having to sacrifice production time to prepare for ISO 9001:2015 certification. This e-filling program packs the concept of self-evaluation so that in the program there are various questions that are in accordance with the clauses in ISO 9001:2015 along with the assessment points. so that auditors no longer need to come to a company to audit the completeness of documents to meet the requirements of the ISO 9001:2015 clause. This program, also helps in the COVID-19 pandemic, where it is not recommended to have direct contact between humans, so with this program, auditors no longer need to have direct contact because everything is done online.